The role of impact assessment in evaluating agricultural R&D - Alwang, Jeffrey; Norton, George W. (International Food Policy Research Institute, 2016)
The purpose of this chapter is to review experience with impact assessment of agricultural research in Africa south of the Sahara (SSA). The analysis emphasizes ex post assessment, but lessons for ex ante analysis and priority setting are also presented. Methods used to evaluate agricultural research are briefly described and critiqued. Thereafter, empirical evidence on the benefits of agricultural research in Africa is summarized and categorized by type of research. Finally, lessons are drawn for the role of impact assessment for agricultural research in Africa.